Digital Marketing Dalam Menghadapi Persaingan Bisnis di Era Digital: Kajian Konseptual - Siregar, Akhmad Irwansyah (Universitas Batanghari Jambi, 2024)
The development of digital technology has significantly changed the competitive landscape of businesses, forcing companies to adapt with more innovative and efficient strategies. Digital marketing emerges as one of the effective approaches in facing this challenge, enabling companies to expand market reach, improve interaction with consumers, and measure marketing performance in real-time. The implementation of digital marketing strategies is an effective solution in achieving this goal. This research examines how digital marketing can be used to strengthen consumer trust, form a strong corporate image, and increase customer loyalty. This research consists of several parts. First, the literature review focuses on digital marketing. Second, the research model and propositions developed in this study are based on the literature review of previous studies, and are discussed in depth in relation to trust, corporate image, and customer loyalty. The study results show that an integrated digital marketing strategy not only helps companies survive the competition, but also builds long-term relationships with customers, which ultimately increases trust and strengthens the company's image in the market. Proper implementation of these strategies is a key factor in business success in the digital age.